The Importance of Self-Awareness regarding Forest Fire Triggerers - Shinta Rahmalia Saputri (Proceeding International Conference Restructuring and Transforming Law, 2024)
Forest fires are events where forests or land burn which results in natural and environmental damage which can cause economic, flora and fauna, socio-cultural, political and climate change losses. This paper uses a qualitative method, namely a method that focuses on in-depth observation of the data and facts that occur. The main factor is the use of land for other purposes, for example; building factories, other plantations, opening roads, etc. But besides all that, there are side effects that arise as a result of forest fires that are set deliberately.